Gender awareness in medicine: adaptation and validation of the Nijmegen Gender Awareness in Medicine Scale to the Portuguese population (N-GAMS) - Morais, R.; Bernardes, S.F.; Verdonk, P. (Advances in Health Sciences Education, 2019)
Health care professionals’ gender awareness has been presented as a mechanism to minimize gender biases in health. The present paper aimed to adapt and validate the Nijmegen Gender Awareness in Medicine Scale (N-GAMS, Verdonk et al. in Sex Roles 58:222–234, 2008. https://doi.org/10.1007/s11199-007-9326-x) to the Portuguese population, also addressing some limitations of its original study, namely by: (1) testing the scale’s three-fold underlying structure and (2) extending the study of its criteria-related validity, by analyzing sex-related differences in medical students’ gender awareness and the associations between gender awareness and empathy and sexism. One thousand and forty-eight medical students (Mage = 22.90; 67.1% women) filled out the Portuguese version of the N-GAMS (N-GAMS.pt) along with measures of Physician Empathy and Sexism. A Parallel Analysis and an Exploratory Factor Analysis suggested the presence of three factors. A Confirmatory Factor Analysis showed a good fit of the hypothesized three-factor structure: (1) gender sensitivity (n = 6 items; ? =.713), (2) gender-role ideologies towards patients (n = 7 items; ? =.858) and (3) gender-role ideologies towards doctors (n = 5 items; ? =.837), with a positive association between the latter two (r =.570; p <.001). The N-GAMS.pt also showed good criteria-related validity. Namely, as hypothesized: (1) more empathic students reported more gender sensitivity and lower endorsement of gender-role ideologies; (2) higher hostile and benevolent sexism were associated to higher endorsement of gender-role ideologies; and (3) higher hostile sexism was associated to lower gender sensitivity. Implications of the N-GAMS for research and interventional purposes are discussed.